An approach to understanding tribological behaviour of dental composites through volumetric wear loss and wear mechanism determination; beyond material ranking. (April 2017) - Altaie, Asmaa; Bubb, Nigel L.; Franklin, Paul; Dowling, Adam H.; Fleming, Garry J.P.; Wood, David J.
Abstract: Objective: To investigate the fundamental wear mechanisms of six resin-based composite (RBC) formulations during short-term in vitro wear testing. Materials: RBC materials were condensed into rectangular bar-shaped specimens and light irradiated using the ISO 4049 specimen manufacture and irradiation protocol. Wear testing ( n  = 10 specimens for each RBC) was performed on a modified pin-on-plate wear test apparatus and wear facets were analysed for wear volume loss using a white light profilometer. The wear tested RBC specimens and their corresponding antagonists were analysed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS), respectively to determine the wear mechanism. Results: Data generated using the profilometer showed variations in the mean total wear volume (mm 3 ) between the RBCs tested ( p  < 0.05). Abrasive wear was evident in all RBCs investigated with varying degrees of damage. Material transfer/deposition of the filler particles on the corresponding antagonists was evident in two RBC materials (Filtek Supreme and Kalore) indicative of a further adhesive wear mechanism. Conclusion: It is proposed that the approach employed to use a combination of measurement and analytical techniques to quantify the wear facet volume (profilometry), wear trough (SEM) and material transfer (EDS) provides more useful information on the wear mechanism and the tribology of the system rather than relying on a simple wear ranking for the RBC materials as is routinely the case in dental research studies.